PENGARUH SALES PROMOTION VOUCHER "SHOPEEPAY DEALS RP 1" TERHADAP MINAT BERBELANJA (Survei Pada Followers Akun Twitter @ShopeeID) - Meilan Tri Wulandari (2021)
ShopeePay Deals Rp. 1 is one of the voucher promos carried out by Shopee, users of the promo can buy vouchers at a price of 1 rupiah. This study aims to examine the effect of sales promotion vouchers "Shopeepay deals Rp. 1 on shopping interest. The background of this research is that researchers want to know how much influence sales promotion vouchers "ShopeePay deals Rp. 1" have on shopping interest, especially Shopee application users. used to explain this research is the Technology Acceptance Model (TAM). This research uses a quantitative approach and survey method by distributing questionnaires to 100 respondents who use the Shopee application. Through the results of the correlation test, it is known that the correlation value is 0.788 which means that the relationship between sales promotion variables vouchers with shopping interest variables have a strong relationship. After doing research, the researchers found that sales promotion affect shopping interest, which is known from the results of hypothesis testing namely 12,670 (t count) > 1,664 (t table). The results of the determination test are 62% of the effect given by the sales promotion voucher "ShopeePay deals 1" on shopping interest and the remaining 38% is influenced by other factors. It can be concluded that the sales promotion voucher ShopeePay Deals Rp 1 has the highest category of respondents. And with this research, the researcher suggests for further research as reference material and reference method as the Elaboration Likelihood Model (ELM) or this research can be carried out with ShopeePay objects which are more in-depth and keep abreast of increasingly dynamic.